Synthesis, Characterization, Multifunctional Bioactivity and Computation Study of 5-Fluorouracil-Thiamine HCl Mixed Ligands Complexes - Ayinla, Sheriff; Rajee, Abdullah; Hitler, Louis; Bassey, Francisca; BUSARI, Hassan (FUDMA Journal of Sciences, 2026)
This study explored the structural, spectroscopic and biological properties of Ni(II) and Zn(II) mixed-ligand complexes of 5-fluorouracil–thiamine HCl synthesized through one-pot synthetic method using integrated approaches including computational study. 5-fluorouracil acts as bidentate ligand through nitrogen and carbonyl oxygen atoms of the pyrimidine ring while the thiamine HCl acts as monodentate through nitrogen atom of its pyridinic ring. Geometry optimization demonstrated that the Ni(II) complex exhibits shorter and stronger metal–ligand bonds, particularly with nitrogen and oxygen donor atoms, reflecting enhanced covalent character and greater structural distortion compared to the Zn(II) complex, which showed relatively longer and more ionic interactions. The Ni(II) complex exhibited better antimicrobial and antioxidant properties compared to the Zn (II) complex and the 5-flourouracil ligand. The molecular docking studies indicated that the two complexes showed superior binding affinities against both bacterial (1KZN) and fungal (5TZ1) target proteins compared to standard drugs but Ni (II) complex exhibited excellent antibacterial activity with a Moldock score of −153.39 kcal/mol and strong hydrogen bonding interactions (Val 71, Thr 65, and Asn 46), outperforming the standard drug Ciprofloxacin, which showed a lower binding affinity (−117.39 kcal/mol) and fewer hydrogen bonds. Similarly, both complexes demonstrated remarkable antifungal activity, with Zn (II) complex showing particularly strong binding (−131.12 kcal/mol) and favorable interactions with key residues (Ile 471, Tyr 132, and Arg 381), surpassing the performance of the Fluconazole standard, which exhibited weaker interaction profiles.